The Joint Effects of Social Norm Appeals and Fear Appeals in COVID-19 Vaccine Campaign Posters on Self-Perceived Communication Quality and Vaccination Intention - Liu, Jiawei; Yang, Xiaobing; Lu, Yanqin; Zheng, Xia (Frontiers in Psychology, 2022)
To understand how different types of cues in vaccine education messages affect attitude toward campaign messages and vaccination intention, the current study examined the impact of the presence of social norm appeals (individual vs. group cues) and the presence of fear appeals in COVID-19 vaccine campaign posters on perceived communication quality and vaccination intention. A 2 (Social norm appeal: individual cue vs. group cue) x 2 (Fear appeal: absence vs. presence) x 3 (Repetition) within-subject factorial design experiment was conducted in China. Findings demonstrated that the presence of fear appeals in COVID-19 vaccine campaign posters elicited lower levels of perceived communication quality and vaccination intention than those without fear appeals. The interactive effect of fear appeals and social norm appeals was also found to be significant. Specifically, positive-framed messages (i.e., absence of fear appeals) with group cues and fear appeal messages with individual cues elicited higher perceived information quality and stronger vaccination intention than other types of messages. Understanding how these cues function jointly in COVID-19 vaccine campaign messages will help public health practitioners create more effective intervention strategies.